Towards a Holistic Halal Certification Self-Declare System: An Analysis of Maqasid al-Sharīʿah-Based Approaches in Indonesia and Malaysia - Hasan, Maisyarah Rahmi; Abd Latif, Mohd Syahiran (Mazahib, 2024)
Despite the transparent and legal-compliant implementation of the Halal certification system in Indonesia and Malaysia, there are obstacles in practice, such as quality control and supervision for Halal-certified products. Therefore, it is necessary to implement a comprehensive Halal certification system founded on Maqasid al-Sharīʿah. This study employs normative-doctrinal legal research to provide recommendations for resolving issues associated with implementing the Halal certification system in Indonesia and Malaysia. It reveals that both Indonesia and Malaysia have institutions tasked with administering the Halal certification system; in Indonesia, it is administered by Badan Penyelenggara Jaminan Produk Halal (Halal Product Guarantee Organizing Agency or BPJPH), and in Malaysia, Jabatan Kemajuan Islam Malaysia (Department of Islamic Development Malaysia or JAKIM). Quality control and supervision are obstacles to implementing Halal certification in Indonesia and Malaysia, particularly self-declaration. Due to the misuse of Halal labels and the incorporation of non-submitted materials and products, rigorous oversight is necessary for the products that acquired Halal certificates using this scheme. Business actors lack knowledge and comprehension of the Halal guarantee system, which prompts them to implement the objectives of Halal certification. Adopting Maqasid al-Sharīʿah is necessary to put in place a Halal certification system that prioritizes business actors' awareness of the goals of Halal certification, which include the preservation of religion, life, the mind, ancestry, and property. Moreover, this preservation aligns with the goal of Halal certification's contribution to spiritual and worship strength.